2001
DOI: 10.1097/00043764-200105000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Recent Dioxin Contamination From Agent Orange in Residents of a Southern Vietnam City

Abstract: Marked elevation of dioxin associated with the herbicide Agent Orange was recently found in 19 of 20 blood samples from persons living in Bien Hoa, a large city in southern Vietnam. This city is located near an air base that was used for Agent Orange spray missions between 1962 and 1970. A spill of Agent Orange occurred at this air base more than 30 years before blood samples were collected in 1999. Samples were collected, frozen, and sent to a World Health Organization--certified dioxin laboratory for congene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
3
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 19 publications
4
70
3
1
Order By: Relevance
“…Several studies reported that the half-life of dioxin in humans is 7-11 years for adults (Pirkle et al 1989;Kreuzer et al 1997). Despite the fact that a significant amount of time has passed since the end of the war, herbicide residues still exert adverse effects on those subjects living in the sprayed/hot-spot areas and on the country's ecosystem as a whole (Schecter et al 2001;Mai et al 2007). Dioxin hot-spots contain high TCDD levels due to the inevitable spillages that occurred during loading of the herbicide into crop-spraying planes during the Vietnam War (Dwernychuk 2005), and our study showed that mean dioxin levels in breast milk of primiparas were higher in the hot-spot than in the nonsprayed area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported that the half-life of dioxin in humans is 7-11 years for adults (Pirkle et al 1989;Kreuzer et al 1997). Despite the fact that a significant amount of time has passed since the end of the war, herbicide residues still exert adverse effects on those subjects living in the sprayed/hot-spot areas and on the country's ecosystem as a whole (Schecter et al 2001;Mai et al 2007). Dioxin hot-spots contain high TCDD levels due to the inevitable spillages that occurred during loading of the herbicide into crop-spraying planes during the Vietnam War (Dwernychuk 2005), and our study showed that mean dioxin levels in breast milk of primiparas were higher in the hot-spot than in the nonsprayed area.…”
Section: Discussionmentioning
confidence: 99%
“…As herbicides are known to have been spilled at those sites where soil and sediment dioxin levels are found to be high, individuals residing close to these sites are highly likely to have been exposed to such levels (Dwernychuk 2005;Dwernychuk et al 2006). Indeed, previous studies detected elevated TCDD levels in food, wildlife, and subjects from a contaminated area (Schecter et al 2001(Schecter et al , 2002(Schecter et al , 2003Dwernychuk et al 2002). Furthermore, studies recently demonstrated that the mean dioxin levels in soil and breast milk in a sprayed area are significantly higher than those in a non-sprayed area (Nhu et al 2009;Saito et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to other industrialized countries, the dioxin burden in Chapaevsk residents was also substantially higher than general population levels reported for North America ( Longnecker et al, 2000;Schecter et al, 2002 ), Germany ( the 1996 data ) (Päpke, 1998 ), and Hanoi, Vietnam (Schecter et al, 2001 ). On the contrary, mean WHO -TEQ 98 levels of 2,3,7,8 -TCDD in Chapaevsk residents (8.3 ppt ) were lower, as compared to populations with known high 2,3,7,8 -TCDD exposure, such as South Vietnam residents exposed to Agent Orange ( 69.7 ppt ) (Schecter et al, 2001 ) and residents of the most contaminated zone in Seveso, Italy (53.2 ppt ) ( Landi et al, 1997 ). Goldman et al (2000 ) reported serum PCDD /PCDFs levels for California residents living in close proximity to a wood preservative treatment plant, where there had been a fire involving pentachlorophenol.…”
Section: Characteristicmentioning
confidence: 61%
“…Chapaevsk residents extensively use these areas as garden plots for food production, which is often sold at the local market. Table 4 presents the mean dioxin WHO -TEQ 98 levels in serum of Chapaevsk residents in comparison to reported levels in workers and general population samples from other parts of Russia, North America, Europe, and Asia ( Päpke, 1998;Longnecker et al, 2000;Ryan and Schecter, 2000;Amirova and Kruglov, 2001;Amirova et al, 1998;Revich et al, 2001;Schecter et al, 2001Schecter et al, , 2002. For comparison purposes, previously published data on dioxin TEQ exposure from Russia and other countries, which used the 1994 I -TEFs ( Ahlborg et al, 1994 ), were recalculated using the 1998 WHO -TEFs ( Van den Berg et al, 1998 ).…”
Section: Characteristicmentioning
confidence: 99%
“…Recent surveys in Vietnam by Dwernychuk et al (2002), Schecter et al (2001), and others have shown persistently high levels of dioxin in soil, biota, and humans taken from areas known to have been very heavily sprayed or contaminated by spillage. In March 2002, the United States and the government of Vietnam entered into a collaborative agreement to undertake future epidemiological and ecological studies of the effects of wartime herbicide use in that country (Cyranoski, 2002).…”
Section: Limitationsmentioning
confidence: 99%